2021
DOI: 10.3390/cells10112833
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Bone Marrow Microenvironment in Drug Resistance of Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a heterogeneous disease with a poor prognosis and remarkable resistance to chemotherapeutic agents. Understanding resistance mechanisms against currently available drugs helps to recognize the therapeutic obstacles. Various mechanisms of resistance to chemotherapy or targeted inhibitors have been described for AML cells, including a role for the bone marrow niche in both the initiation and persistence of the disease, and in drug resistance of the leukemic stem cell (LSC) populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 173 publications
(176 reference statements)
0
18
0
Order By: Relevance
“…A cell-type-specific dependence on STAT5 signaling may cause elevated susceptibility to the BCL-2- and BCL-XL inhibitors and a reduced response to PI3K- and MEK inhibitors, in the bone marrow environment. Various cellular components, cytokines, and chemokines present in the bone marrow may impact AML initiation and therapy resistance at the cellular and molecular level [ 43 , 44 ]. We found that only the combination of venetoclax and MCL1 inhibitor S63845 induced cell death with equal efficacy in AML cells grown in the absence or presence of bone marrow stroma, indicating a potential advantage of applying this combination in the treatment of AML, as this may eradicate leukemic stem cells in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…A cell-type-specific dependence on STAT5 signaling may cause elevated susceptibility to the BCL-2- and BCL-XL inhibitors and a reduced response to PI3K- and MEK inhibitors, in the bone marrow environment. Various cellular components, cytokines, and chemokines present in the bone marrow may impact AML initiation and therapy resistance at the cellular and molecular level [ 43 , 44 ]. We found that only the combination of venetoclax and MCL1 inhibitor S63845 induced cell death with equal efficacy in AML cells grown in the absence or presence of bone marrow stroma, indicating a potential advantage of applying this combination in the treatment of AML, as this may eradicate leukemic stem cells in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…This feature makes the T2 combo of special attention pharmaceutically because BM is a tissue where most of the leukemic stem cells reside, and blast cells stop further development, thereby protecting leukemia cells against the cytotoxicity of chemotherapeutic agents and becoming a possible source of relapse. Moreover, BM has been implicated as a privileged microenvironment in resistance to leukemia therapy [ 25 ]. The specific activity of the T2 combo in BM and blood makes this combination highly effective to treat leukemia systematically.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs confer drug resistance to AML cells through a wide variety of mechanisms where the participation of the repertoire of soluble factors and cell interactions is well known [ 258 ]. These VLA-4/VCAM1-mediated interactions [ 204 ] promote AML cells’ chemoresistance by diverse mechanisms, including Bcl-2 overexpression [ 132 ] and JAK/STAT [ 259 ] and NF-κB signalling in MSCs.…”
Section: Msc Roles In Drug Resistancementioning
confidence: 99%
“…Of note, this profile was associated with bad prognosis in AML patients [ 272 ], suggesting that the secretory phenotype of MSCs could exert an important role in the course of the disease. A detailed network participating in AML resistance has been described [ 258 ].…”
Section: Msc Roles In Drug Resistancementioning
confidence: 99%